Secondary hemophagocytic syndrome after renal transplantation: two case-reports - Narciso Júnior,José (2020)
ABSTRACT Hemophagocytic syndrome or hemophagocytic lymphohistiocytosis (HLH) is an infrequent and underdiagnosed condition caused by an overactive immune response, resulting in blood cells phagocytosis. After kidney transplantation (KTx), HLH is usually secondary (or reactive) to infectious and neoplastic processes and has a high mortality rate. No effective treatment is available for this condition. Usual procedures include detecting and treating the pathology triggering the immune system dysregulation, other than administration of intravenous human immunoglobulin (IVIG) and high doses of steroids, and plasmapheresis. The best protocol for maintenance immunosuppressive therapy is also unknown. This article presents two cases of post-KTx reactive HLH that underwent adjuvant IVIG treatment and obtained good clinical results. Despite the high morbidity and mortality associated with reactive HLH after KTx, the early and precise diagnosis and the administration of IVIG therapy along with the treatment of the triggering disease, was an effective strategy to control HLH.